Corpus callosum volumes in bipolar disorders and suicidal vulnerability. (30th April 2017) - Gifuni, Anthony J.; Olié, Emilie; Ding, Yang; Cyprien, Fabienne; le Bars, Emmanuelle; Bonafé, Alain; Courtet, Philippe; Jollant, Fabrice
Abstract: Reduced size of the corpus callosum (CC) has been associated with bipolar disorders and suicidality. Here, we aimed at investigating the relative independence of these associations in a large sample of patients. Two samples of males and females totaling 209 euthymic participants were recruited, including 72 patients with a major depressive disorder, 64 with bipolar disorders and 73 healthy controls. Among patients, 61 had a lifetime history of suicide attempt and 75 had none. Structural scans were acquired with 1.5 T magnetic resonance imaging. Surface-based morphometry (Freesurfer) analysis was used to compute the volumes of the CC. In the whole sample, there was a significant reduction in the volume of mid-anterior, central, and mid-posterior (all p<0.008) CC in bipolar patients independently from suicidality, with medium effect sizes between unipolar and bipolar patients (Cohen's d between 0.46 and 0.62). In contrast, suicide attempters did not differ from non-attempters. This significant association between CC volumes and bipolar disorders was mainly found in the male sample, while a trend was found in the female sample. Within each patient group, medication had no major effect. Our study adds to the growing body of evidence linking corpus callosum alterations and bipolar disorders. Highlights: Corpus callosum volumes were measured in a large sample of mood disordered patients and controls. Bipolarity was associated with smaller corpus callosum compared to major depression. This volume reduction was located in the central portion of the corpus callosum. Suicide attempters did not differ from non-attempters in terms of corpus callosum volume.